Literature Review: Human Resource Management Strategies in the Digital Era - Firayani Firayani (Oikonomia : Journal of Management Economics and Accounting, 2024)
Digital transformation has brought fundamental changes in human resource (HRM) management, requiring organizations to develop adaptive and innovative managerial strategies. This study aims to identify and analyze HRM management strategies in the digital era through a qualitative approach based on literature review. The review was conducted systematically across various scientific sources such as journal articles, academic books, and relevant industry reports covering the period 2015–2025. The results indicate that HRM strategies in the digital era emphasize strengthening digital competencies, implementing data-driven HRM analytics, working flexibility, and building an organizational culture that supports innovation and virtual collaboration. The HRM function is no longer administrative but becomes a strategic partner in decision-making and organizational transformation. However, implementation challenges remain related to technological readiness, resource constraints, and cultural resistance. Therefore, an effective digital HRM strategy must be contextual, data-driven, and sustainable. This research is expected to provide a conceptual contribution to the development of HRM management policies relevant to the demands of the digital era and open up space for further case-based research and empirical approaches.